ANALISIS HUBUNGAN KAUSALITAS SEKTOR KEUANGAN DAN PERTUMBUHAN EKONOMI DI INDONESIA - Hendra Kesuma (Universitas Negeri Medan, 2013)
The financial sector plays a very significant role in triggering the economic growth of a country and also became the locomotive of growth in the real sector through capital accumulation and technological innovation. High performance financial sector will result in increased economic growth instead of economic growth is not the main cause of the improvement in the performance of the financial sector. This study aims to examine the relationship of causality between financial sector and economic growth in Indonesia, where the financial sector in the show by the monetization ratio, the ratio of loans, demand deposits and savings. By using secondary data for the period 2000-2010, This research uses the analytical framework cointegration and Vector Error Correction Model (VECM) between financial sector development and economic growth. The results showed that the financial sector indicated by the ratio of monetization, credit ratios, demand deposits and savings have no causal relationship with economic growth in Indonesia. Significant influence given variable demand deposits to economic growth. Instead of economic growth significantly affect the monetization and savings.